COMPARATIVE EVALUATION OF TITANIUM AND BIORESORBABLE FIXATION IN LEFORT I OSTEOTOMY: A RANDOMIZED CLINICAL STUDY - Mannobjonova Mukhina Abdullojon Qizi; Sokhibov O.M (TADQIQOTLAR, 2025)
ANNOTATION LeFort I osteotomy is a widely used surgical procedure for correcting maxillary deformities.  Stable  fixation  is  essential  for  maintaining  postoperative  skeletal positioning.  Titanium  plates  provide  excellent  mechanical  strength  but  remain permanently in the facial tissues and often require removal. Bioresorbable plates were developed to avoid long-term hardware retention, although concerns remain regarding their initial stability. This study compares titanium and bioresorbable fixation systems in patients undergoing LeFort I osteotomy. Clinical and radiographic evaluations were conducted to assess skeletal stability, postoperative comfort, and complications. The findings show that titanium fixation offers superior early stability, while bioresorbable fixation  improves  patient  comfort  and  eliminates  the  need  for  secondary  removal. Long-term  skeletal  stability  was  comparable  in  both  groups,  indicating  that  both systems  are  effective  and  should  be  chosen  based  on  patient  needs  and  surgeon preference.